2014
DOI: 10.1007/s40141-014-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Mechanisms Contributing to Spasticity and Implications for Treatment

Abstract: Histolopathological studies have demonstrated a generalized increase in extracellular connective tissue in spastic muscles. It is known that increased connective tissue in an immobilized and contracted muscle reduces its compliance and could reduce the threshold for stimulation of spindle receptors in the muscle. Various authors have investigated how increased stretch-induced stimulation of spindles in muscles with stiffer connective tissue can contribute to spasticity. In this review, we compile evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 76 publications
0
48
0
Order By: Relevance
“…Immobility in turn can begin a vicious circle of problems including peripheral soft-tissue changes that reduce tissue compliance, potentiation of reflex mechanisms and spasticity, eventually leading to muscle fibrosis and contributing to abnormal limb posturing, pain and decreased function (Figure 2) (Stecco, Stecco et al 2014). Spasticity is now thought to arise as a consequence of contractures rather than being a cause of contractures (Ward 2012).…”
Section: Learned Nonusementioning
confidence: 99%
“…Immobility in turn can begin a vicious circle of problems including peripheral soft-tissue changes that reduce tissue compliance, potentiation of reflex mechanisms and spasticity, eventually leading to muscle fibrosis and contributing to abnormal limb posturing, pain and decreased function (Figure 2) (Stecco, Stecco et al 2014). Spasticity is now thought to arise as a consequence of contractures rather than being a cause of contractures (Ward 2012).…”
Section: Learned Nonusementioning
confidence: 99%
“…Over time, there are also changes in the arrangement of collagen fibrils in the endomysium. Changes in the turnover of HA and in the properties of extracellular matrix may lead to structural and functional changes in the muscles, which has a significant impact on the movement [17,19]. Alteration of HA could also modify the activation of the receptors, producing nonspecific musculoskeletal pain [11,17,20].…”
Section: Discussionmentioning
confidence: 99%
“…There is now emerging evidence that the accumulation of hyaluronan precedes fibrosis in several organs including the lung, kidney, and liver (Bensadoun et al, 1996;Evanko et al, 2015;Jun et al, 1997;Hernnas et al, 1992;Halfon et al, 2005). Although the mechanisms underlying changes in muscle due to mechanical immobilization and spastic paralysis may be different, immobility is a consequence of spastic paralysis, and may trigger a cascade of events that leads to the accumulation of hyaluronan (Stecco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It both prevents full passive movement (leading to abnormal posturing that can become fixed over time) and makes active movement more difficult in patients who are already weak from the neurologic injury. Non-neural peripheral mechanisms are thought to cause muscle stiffness (Burke et al, 2013;Stecco et al, 2014), although this has not been shown conclusively.…”
Section: Introductionmentioning
confidence: 99%